1994
DOI: 10.1159/000211315
|View full text |Cite
|
Sign up to set email alerts
|

Minoxidil Sulfation in the Hair Follicle

Abstract: The in vivo model which may be the most accurate for the ability to predict hair growth in humans, and which was utilized in the preclinical development of minoxidil, is the adult stumptailed macaque. Previous reports have suggested that the enzyme activity which accounts for the activation of minoxidil, i.e., minoxidil sulfotransferase, is present in skin. We have demonstrated that scalp skin from the stumptailed macaque contains minoxidil sulfotransferase activity, and further with dissection of that scalp s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
2

Year Published

1997
1997
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 11 publications
0
16
0
2
Order By: Relevance
“…For the antihypertensive and hypertrichotic drug minoxidil, bioactivation by sulfation is beneficial, since the sulfate ester is the pharmacologically active species (74). Elegant experiments demonstrated that the ST responsible for this reaction is expressed in the hair follicles, providing in situ activation of topically applied minoxidil (75), which has found clinical application in the treatment of baldness.…”
Section: Biologically Active and Toxic Sulfatesmentioning
confidence: 99%
“…For the antihypertensive and hypertrichotic drug minoxidil, bioactivation by sulfation is beneficial, since the sulfate ester is the pharmacologically active species (74). Elegant experiments demonstrated that the ST responsible for this reaction is expressed in the hair follicles, providing in situ activation of topically applied minoxidil (75), which has found clinical application in the treatment of baldness.…”
Section: Biologically Active and Toxic Sulfatesmentioning
confidence: 99%
“…Another possibility is that, analogous to other N-oxides such as minoxidil (Hamamoto and Mori, 1989;Johnson et al, 1992;Baker et al, 1994), the N-oxide of lamotrigine could be a substrate for sulfotransferases leading to a N-sulfate, which might have sufficient chemical reactivity to bind to protein (Fig. 2).…”
mentioning
confidence: 99%
“…Превращение минок-сидила в миноксидил сульфат катализируется фер-ментами сульфотрансферазами. Миноксидил-суль-фотрансферазная активность была обнаружена в гомогенатах печени крыс, человека, тромбоцитах, в фолликулах вибрисс мышей и крыс, в их эпидер-мальных кератиноцитах и эпителиальном влагали-ще корня волоса, в ВФ -в скальпе короткохвостых макак [12,[14][15][16][17][18][19][20].…”
Section: как это работает?unclassified
“…При этом для четырех сульфотрансфераз экспрессия мРНК была обнару-жена в эпидермальных кератиноцитах человека [21]. Во внешней оболочке корня ВФ превращение ми-ноксидила в активную форму миноксидила сульфа-та происходит при помощи эндогенных сульфо-трансферазных ферментов [22][23][24]. Интересные наблюдения были сделаны A. Buhl и соавт.…”
Section: как это работает?unclassified